The Welding Defect Analysis on ASTM A106 Grade B with Inconel 82 Using Metallography Test and Microhardness Test - Arief Muliawan; Rizki Ilmianih (Politeknik Piksi Ganesha Indonesia, 2024)
Welding inspection is an important practice to assess the integration of structures and their components in many industrial applications. The quality of industrial pipes must be able to withstand high pressures and temperatures, such as in the riser tube primary reformer. In this study, inspection of welding results on ASTM A106 grade B pipes with Inconel 82 using metallography and microhardness was carried out. Based on the results of visual tests and penetrant tests, cracks were found in the meeting area between the Inconel 82 weld and ASTM A106 grade B. The results of the metallography test in the meeting area between Inconel 82 and ASTM A106 grade B showed continuous microcracks and continuous macrocracks. The results of microhardness testing in the area around the crack had a lower hardness value than the area far from the crack. The welding connection of ASTM A106 grade B with Inconel 82 could not be used optimally at a temperature of 748oC because Inconel 82 has a silicon element of 0.5% which causes a difference in solidification between ASTM A106 grade B and Inconel 82